Cesarzowa Bułgarów, augusta i bazylisa – Maria-Irena Lekapena i transfer bizantyńskiej idei kobiety-władczyni (imperial feminine) w średniowiecznej Bułgarii - Zofia A. Brzozowska (Slavia Meridionalis, 2017)
Empress of Bulgarians, augusta and basilissa – Maria-Irene Lekapene and the transfer of the idea of imperial feminine in the Medieval Bulgaria